Abnormal metabolic network activity in Parkinson’s disease: test–retest reproducibility - Ma, Yilong (J Cereb Blood Flow Metab, 2006)
Parkinson’s disease (PD) is associated with an abnormal pattern of regional brain function. The expression of this PD-related covariance pattern (PDRP) has been used to assess disease progression and the response to treatment. In this study, we validated the PDRP network as a measure of parkinsonism by prospectively computing its expression (PDRP scores) in (15)O-water (H(2) (15)O) and (18)F-fluorodeoxyglucose (FDG) positron emission tomography (PET) scans from PD patients and healthy volunteers. The reliability of this measure was also assessed within subjects using a test–retest design in mildly affected and advanced PD patients scanned at baseline and during treatment with levodopa or deep brain stimulation (DBS). We found that PDRP expression was significantly elevated in PD patients (P < 0.001) relative to controls in a prospective analysis of brain scans obtained with either H(2) (15)O or FDG PET. A significant correlation (R(2) = 0.61; P < 0.001) was evident between PDRP scores computed from H(2) (15)O and FDG images in PD subjects scanned with both tracers. Test–retest reproducibility was very high (intraclass correlation coefficient (ICC) > 0.92) for PDRP scores measured both within PET session and between sessions separated by up to 2 months. This high reproducibility was observed in both early stage and advanced PD patients scanned at baseline and during treatment. The within-subject variability of this measure was less than 10% for both unmedicated and treated conditions. These findings suggest that the PDRP network is a reproducible and stable descriptor of regional functional abnormalities in parkinsonism. The quantification of PDRP expression in PD patients can serve as a potential biomarker in PET intervention studies for this disorder.